GLORIOSA SUPERBA: REMEDY OR POISON? - Maroyi, A.; van der Maesen, J. J. G. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The tropical African and Asian plant species, Gloriosa superba L. (Colchicaceae) is not only a notorious human and livestock poison, but is also widely used as herbal medicine. The plant’s medicinal uses and poisonous properties were collated over its distributional range. Gloriosa has caused illnesses and even fatalities in humans and animals due to both intentional and accidental poisoning. Its tubers have been used for centuries for homicide, suicide and inducing abortion. On the other hand, Gloriosa is frequently used against digestive, respiratory, cardiovascular troubles and as a sedative medicine. Traditional healers seem to be aware of its toxicity as the amounts they prescribe are such that toxic symptoms are minimized. Using larger dosages usually result in poisoning. Its poisonous properties are due to colchicine and gloriosine, the tropolon alkaloids regarded as the biological hallmark of Gloriosa. These alkaloids act slowly, the first toxic symptoms appearing many hours after administration of the species. Death occurs at the earliest in 12 hours from circulatory collapse, respiratory or cardiac arrest [1]. The tropolon alkaloids are unusually rapidly absorbed after oral administration, strongly bound to plasma and cell protein, eliminated through the gall-bladder and reabsorbed through the intestines which explains the long-lasting effect of a single dose or the accumulation of smaller colchicine doses and may also explain the severe gastrointestinal side effects [1]. With such potentially dangerous substances, care in the use of Gloriosa as medicine is essential to avoid complications of overdose. References: [1] Goodman, L.S. and Gilman, A.: The Pharmacological Basis of Therapeutics. Fifth Edition. McMillan Publishing Co. Inc. / Bailliere Tindall, New York / London 350-352 (1975)